2020
DOI: 10.1021/acsami.0c15945
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Zeolitic Imidazolate Framework-8 Activator of Canonical MAPK Signaling for Bone Repair

Abstract: Zeolitic imidazolate framework-8 (ZIF-8) is an important type of metal organic framework and has found numerous applications in the biomedical field. Our previous studies have demonstrated that nano ZIF-8-based titanium implants could promote osseointegration; however, its osteogenic capacity and the related mechanisms in bone regeneration have not been fully clarified. Presented here is a nanoscale ZIF-8 that could drive rat bone mesenchymal stem cell (rBMSC) differentiation into osteoblasts both in vitro and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 64 publications
3
71
0
Order By: Relevance
“…53 Simultaneously, previous studies have confirmed that ZIF-8 NPs could effectively improve the osteogenic function of related cells by activating MAPK signaling. 54 As expected, the PPZF JNF showed the most significant osteoconductive ability compared to the other groups. This phenomenon could be explained by the fact that in addition to promoting the osteogenesis, FK506 can also reduce the expression of pro-inflammatory factors to alleviate the inflammatory response, which helps establish a stable environment for bone rebuilding.…”
Section: Discussionsupporting
confidence: 73%
“…53 Simultaneously, previous studies have confirmed that ZIF-8 NPs could effectively improve the osteogenic function of related cells by activating MAPK signaling. 54 As expected, the PPZF JNF showed the most significant osteoconductive ability compared to the other groups. This phenomenon could be explained by the fact that in addition to promoting the osteogenesis, FK506 can also reduce the expression of pro-inflammatory factors to alleviate the inflammatory response, which helps establish a stable environment for bone rebuilding.…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies have confirmed that Zn 2+ improves the osteogenic function of cells by activating multiple pathways, such as the canonical Wnt pathway (WNT), mitogen‐activated protein kinase (MAPK), and protein kinase B (AKT) pathways. [ 41 ] However, the mechanisms underlying the osteogenic effects of ZIF‐8 have not been fully elucidated, and further work is required ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Because GO and KEGG analyses (Figure b,c) are predictable based on specific algorithms, Ingenuity Pathway Analysis (IPA, v01-04, QIANGEN Redwood City, CA, USA) software was utilized to reveal the true experimentally verified signal pathways and create the molecular interaction network (Figure d,e). Figure d shows that PMMA&LDH activated the p38 MAPK, extracellular signal-regulated kinases (ERK)/MAPK, , FGF, and TGF-β signaling, all of which promote the osteogenic differentiation of hBMSCs. Additionally, Figure e vividly demonstrates the molecular interaction network and subcellular localization of differentially expressed genes involved in osteogenesis-related signal pathways.…”
Section: Resultsmentioning
confidence: 99%